Collaging atmosphere: Exploring the architectural touch of the eye. (November 2021) - Stenslund, Anette
In recent decades, research has paid attention to the atmospheric ways computer-generated imagery (CGI) marks the experience of future urban design. What has been addressed in the generic abbreviation CGI has, however, exclusively concerned visualisations that communicate with stakeholders beyond designers and architects. Based on fieldwork within an urban design lab, the paper differentiates among the range of CGI used by urban designers. Focusing on collage, which forms one kind of CGI that has received scant attention in scholarly literature, I demonstrate its key function as an epistemological in-house work-in-progress tool that helps designers to refine their vision and to identify the atmosphere of future urban spaces. Based on New Aesthetics, collaging atmosphere is characterised by a physiognomic approach to urban space that selectively addresses aesthetic characteristics. Hence, the paper tackles a discussion that points towards cautious handling of the communicative scope of collages that can be well complemented by other types of CGI before entering a constructive dialogue with clients.